Hierarchically Responsive Tumor‐Microenvironment‐Activated Nano‐Artificial Virus for Precise Exogenous and Endogenous Apoptosis Coactivation. (26th June 2021) - Yang, Jin; Song, Linjiang; Shen, Meiling; Gou, Xinyu; Bai, Liping; Wang, Li; Zhang, Wenli; Wu, Qinjie; Gong, Changyang
Abstract: Targeting apoptotic pathways in tumor cells is recognized as a potent anticancer strategy. However, monotherapies that target a single apoptotic pathway often do not meet expectations and the nonspecific and uncontrolled activation of apoptotic pathways can overshadow potential application prospects. Here, a novel tumor‐microenvironment‐activated nano‐artificial virus (TMAN) with hierarchically responsive capacity is fabricated and loaded with the plasmid encoding tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) and mitochondria‐targeted red fluorescent phototoxic protein (KillerRed) simultaneously for precise and controllable exogenous and endogenous apoptosis coactivation. The inert TMAN is endowed with in vivo longevity and undergoes orderly acidity‐triggered deshielding of a masking layer, enzyme‐responsive charge‐reversal, and oxidative stress‐sensitive structural fragmentation in the tumor extra/intracellular microenvironment to exert precise tumor recognition, deep penetration, cellular internalization, rapid endosomes escape, and effective gene release ability, leading to the effective and tumor‐specific delivery of payloads. Given the virtues of TMAN, a favorable collaboration of TRAIL‐triggered exogenous apoptosis and mitochondria‐targeted KillerRed induced endogenous apoptosis is achieved synchronously under the control of light irradiation, thus remarkably improving antitumor efficacy with minimal toxicity. Taken together, this strategy highlights the significance of exogenous and endogenous apoptosis coactivation in cancer treatments and offers a promising paradigm for precise exo/endogenous dual‐augmented antitumor therapy. Abstract : The reported tumor‐microenvironment‐activated nano‐artificial virus (TMAN) possesses in vivo longevity and can orderly display cascade‐responsive performance to exert precise tumor recognition, deep penetration, cellular internalization, effective endosomes escape, and gene release, leading to the tumor‐specific delivery of payloads. Under the control of light irradiation, TRAIL‐triggered exogenous apoptosis and mitochondria‐targeted KillerRed induced endogenous apoptosis are synchronously activated, thus remarkably improving antitumor efficacy.